An index-based method to assess risks of climate-related hazards in coastal zones: The case of Tetouan. (20th June 2016) - Satta, Alessio; Snoussi, Maria; Puddu, Manuela; Flayou, Latifa; Hout, Radouane
Abstract: The regional risk assessment carried out within the ClimVar & ICZM Project identified the coastal zone of Tetouan as a hotspot of the Mediterranean Moroccan coast and so it was chosen for the application of the Multi-Scale Coastal Risk Index for Local Scale (CRI-LS). The local scale approach provides a useful tool for local coastal planning and management by exploring the effects and the extensions of the hazards and combining hazard, vulnerability and exposure variables in order to identify areas where the risk is relatively high. The coast of Tetouan is one of the coastal areas that have been most rapidly and densely urbanized in Morocco and it is characterized by an erosive shoreline. Local authorities are facing the complex task of balancing development and managing coastal risks, especially coastal erosion and flooding, and then be prepared to the unavoidable impacts of climate change. The first phase of the application of the CRI-LS methodology to Tetouan consisted of defining the coastal hazard zone, which results from the overlaying of the erosion hazard zone and the flooding hazard zone. Nineteen variables were chosen to describe the Hazards, Vulnerability and Exposure factors. The scores corresponding to each variable were calculated and the weights assigned through an expert judgement elicitation. The resulting values are hosted in a geographic information system (GIS) platform that enables the individual variables and aggregated risk scores to be color-coded and mapped across the coastal hazard zone. The results indicated that 10% and 27% of investigated littoral fall under respectively very high and high vulnerability because of combination of high erosion rates with high capital land use. The risk map showed that some areas, especially the flood plains of Restinga, Smir and Martil-Alila, with distances over 5 km from the coast, are characterized by high levels of risk due to the low topography of the flood plains and to the high values of exposure. The CRI-LS provides a set of maps that allow identifying areas within the coastal hazard zone with relative higher risk from climate-related hazards. The method can be used to support coastal planning and management process in selecting the most suitable adaptation measures. Graphical abstract: